Development of Android-Based Learning Media on Smoked Fish Integrated Additive Material in Bengkulu City: Pengembangan Media Pembelajaran Berbasis Android Pada Materi Zat Aditif Terintegrasi Ikan Asap Di Kota Bengkulu - Pancarani, Dwi Ayu; Uliyandari, Mellyta; Parlindungan, Deni; Nirwana, Nirwana; Risdianto, Eko (SEJ (Science Education Journal), 2024)
This research was conducted because of the difficulties experienced by students in learning, especially in the use of learning resources which still use printed books and worksheets in less interesting classroom learning. The gap that occurs between expectations and reality is that students expect learning to be more interactive, interesting and practical. This research aims to produce Android-based learning media products using integrated additives as smoked fish in the city of Bengkulu. The method applied is research and development (RND). This research uses a 4D development model (Define, Design, Development, and Disseminate). Development carried out is limited to the Development stage. The subjects of this research were 31 students in class VIII 2 of SMPN 3 Bengkulu City. Research instruments include observation, teacher interview sheets, student readability test sheets and expert validation sheets. The results of the research show that Android-based learning media on integrated smoked fish additive material is very suitable for use based on validation results from two validators, namely two material experts, two media experts, and practitioners. The learning media validation score by material experts was 88 in the "very feasible" category, the validation result by media experts was 87 in the "very feasible" category. And the practitioner validation results were 91 which were in the "very feasible" category. And the results of student responses to the media were 92 in the "very good" category. It can be concluded that Android-based learning media is very feasible and very good for use in junior high school science learning on additive material. For further training, it is possible to carry out secondary school education learning activities aimed at by the next training.